Selenium alleviates cadmium-induced biological aging acceleration and the potential mediating role of inflammation - Chen Li; Yuerong Xiang; Mingliang Liu; Zhaokun Wang; Yangyang Wu; Qinyi Yang; Lei Huang (Ecotoxicology and Environmental Safety)
Aging and heavy metal pollution are global challenges, and cadmium (Cd) may negatively affect aging. However, effective interventions for Cd toxicity among populations remain insufficient. Selenium (Se) is recognized for its protective effects against heavy metal toxicity and aging. This study utilized data from the National Health and Nutrition Examination Survey (2015–2018) to explore the individual and joint effects of Cd and Se on biological aging acceleration, measured by Klemera-Doubal method biological age acceleration (KDM-BA-Accel) (n = 7119) and Phenotypic age acceleration (PhenoAge-Accel) (n = 7433). Results showed that Cd was positively associated with KDM-BA-Accel (β = 0.57) and PhenoAge-Accel (β = 0.77), while Se had negative associations with both (β values were −4.01 and −5.30, respectively). Nonlinear analyses revealed J-shaped associations for Cd and L-shaped for Se with aging indicators. Moreover, inflammation significantly mediated the Cd-aging and Se-aging relationships. Most importantly, a significant negative interaction between Cd and Se on PhenoAge-Accel (β for interaction = −1.29) suggested an antagonistic effect, particularly among never smokers. Increasing Se content can mitigate the harmful effects of Cd on PhenoAge-Accel were demonstrated through three methods. Specifically, ⅰ) compared to “Cd (-) & Se (-)” group, “Cd (+) & Se (-)” group had β = 0.87, while “Cd (+) & Se (+)” group was non-significant; ⅱ) higher Se content was associated with a lower increase in PhenoAge-Accel as Cd content rose; ⅲ) there were no significant associations between Cd & Se mixture and aging indicators (both p > 0.310). These findings highlight Se supplementation as a potential strategy to counteract Cd-induced aging, offering a new direction for public health interventions in polluted populations.